Faedah Takhrij Hadis kepada Sanad Dan Matan: Satu Kajian Analisis: Benefits of Takhrij Hadith to Sanad and Matn: An Analytical Study - Kawaid, A. Irwan Santeri Doll; Amiruddin Mohd Sobali; Ahmad Izzuddin Abu Bakar (Maʿālim al-Qurʾān wa al-Sunnah, 2021)
Takhrīj hadith (retireieval of hadith) is being considered as a process of disclosing the position of hadith in its premier sources. In this era, this process has become among the matters that are highly demanded to be carried out by various parties to those who are quoting the hadith of the Prophet SAW in their writings. Among the objectives of it is to ease the reader to find the location of the hadith and its source that were quoted from and to preserve the hadith of the Prophet SAW from being manipulated. Meaning that, it can be an evidence to prove that the hadith is truly has its relation to the Prophet SAW and not an invention. Hence, Takhrīj hadith was stressed and became an important matter. Apart from these benefits, there are other benefits related to the Takhrīj that can be obtained in many aspects, especially pertaining with the matn and sanad. This article aims to analyse those benefits as well as describe its positiveness to the ummah dan to the hadith itself.